Optimal control of higher order viable differential inclusions and duality - Mahmudov, Elimhan N. (Informa UK Limited, 2020)
The paper is devoted to the duality of the Mayer problem for κ-th order viable differential inclusions with endpoint constraints, where κ is an arbitrary natural number. Thus, this paper for constr...